A radiofrequência intravaginal na qualidade de vida e função sexual de mulheres com incontinência urinária : um ensaio clínico randomizado - Barroso, Aline Maria Francia (2021)
Urinary incontinence is a problem that affects women more often, with a negative impact on quality of life (QL) and sexual function (SF) in women. There is a consensus in the literature that the treatment of first choice for UI is pelvic physical therapy, with several resources available, among which, the most prominent is the Pelvic Floor Muscle Training (PMT). However, there is a growing demand for techniques that provide faster results and, in this context, radiofrequency has proven to be an effective technique. This study aims to investigate the impact on QoL and SF in women with urinary incontinence, after treatment using intravaginal radiofrequency and, for this, specific instruments were used: the IQoL (Incontinence Quality of Life Questionnaires) to assess QL and the FSFI (Female Sexual Function Index) to assess SF, before and after treatment. The study group performed four sessions, once a week, of Radiofrequency (RF) + PMT, and the control group met with the same PMT protocol. The sample consisted of 60 women, 30 in the PMT group and 30 in the RF + PMT group. In the comparison between before and after treatment, using the IQoL instrument, both groups had a statistically significant difference (p <5%) in the total score and in all domains, showing improvement. When compared by the FSFI instrument, none of the groups showed improvement in the desire domain (p=0.180) and only the RF + PMT group showed a difference in the satisfaction domain. All other domains showed a statistically significant indication (p<5%) of improvement after treatment in both groups. This research also compared the two groups after the treatments performed and there was no statistically significant difference (p>5%) between the groups after analysis with both instruments. Thus, we can say that both treatments improved QoL related to health and sexual function of the participants. These results indicate that radiofrequency associated with PMT has a positive impact on the QoL and sexual function of women with UI in a shorter time of treatment, and can be investigated as a viable alternative to standard physical therapy treatment.